The role of the European Union in international development support system - Kociszewski, Karol (Publishing House of the Wrocław University of Economics, 2009)
One of the most important problems of global economy and society is poverty of one sixth of the world’s population (over 1.1 billion people). To overcome poverty and danger connected with it, the policy supporting underdeveloped countries is carried out from the fifties of the 20th century. At the beginning, it was based on neo-liberal conceptions – development would have been initiated through leading in the solutions which functioned successfully in developed countries. The most important paradigm was Washington Consensus but its results on growth, employment and poverty reduction in many countries were very disappointing. Nowadays, the international policy is based on Millennium Development Goals. The paper’s goal is to show the key role of EU in international development assistance system at the background of comparison with other donors’ activities and global policy efficiency. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 237-246